STRENGTHENING MULTICULTURAL EDUCATION FOR STUDENTS: A Study on the Implementation of Kurikulum Merdeka towards the Application of the "Deep Learning" Approach - Aunurrahman Aunurrahman (JETL (Journal of Education, Teaching and Learning), 2025)
This research aims to obtain information on strengthening multicultural education for students in the perspective of Kurikulum Merdeka and the readiness of implementing the "Deep Learning" approach in the education/learning process in schools in West Kalimantan. An in-depth study focuses on the implementation of Kurikulum Merdeka, forms of multicultural education strengthening, and fundamental principles that have been carried out in the curriculum that align with the "Deep Learning" approach. Information about the performance achievements of implementing Kurikulum Merdeka will become a framework for further improving the learning process towards the application of the "Deep Learning" approach, which is an educational policy that will be applied more intensively. Based on this thinking, the approach and method used in this research are qualitative, with in-depth data collection in schools in West Kalimantan, both in cities and districts. The data obtained are collected and analyzed qualitatively, and validated to provide ease for readers to understand the meaning of the data presented.The results show that: (1) The implementation of Kurikulum Merdeka shows significant achievements in improving the quality of learning and student competence, with educational units able to develop relevant and effective curricula, as well as increased flexibility and autonomy of educational units. However, the obstacles faced include limited resources (trained educators, modern learning facilities, and supporting technology) and the lack of guidance and continuous training for teachers; (2) Strengthening multicultural education is done through the integration of global diversity values in the learning process and activities outside the classroom; (3) Kurikulum Merdeka applies the "Deep Learning" principle through holistic, contextual, and project-based learning that encourages the development of high-level thinking skills, metacognitive abilities, and collaboration.